A new way to see the clouds: the hyper-angular rainbow polarimeter (HARP2) on the NASA PACE satellite mission - Smith, Rachel E.; McBride, Brent A.; Xu, Xiaoguang; Puthukkudy, Anin; Sienkiewicz, Noah; Cieslak, J. Dominik; Remer, Lorraine A.; Fernandez-Borda, Roberto; Martins, J. Vanderlei (Frontiers in Remote Sensing, 2026)
The Hyper-Angular Rainbow Polarimeter 2 (HARP2) on the NASA Plankton Aerosol Cloud ocean Ecosystem (PACE) mission is a wide field of view imaging polarimeter instrument designed for highly accurate and resolved cloud observations. HARP2 is uniquely sensitive to the polarized cloudbow, a ring-like structure in polarized light that appears above liquid water clouds. The structure of the cloudbow encodes information about the droplet size distribution, which is a critical link between cloud microphysical and radiative properties. Matching a multi-angle measurement of the cloudbow to Mie scattering predictions allows for a retrieval of important cloud properties: droplet effective radius and variance. HARP2 is the first instrument of its kind suitable for this retrieval at 5 km spatial resolution. Its wide swath facilitates global coverage of polarimetric measurements in 2 days, making it a uniquely powerful tool for studying cloud microphysics. This paper briefly presents the HARP2 instrument, demonstrates its retrieval capabilities, and discusses future science that it makes possible.